Code development and characteristics analysis for Leak Before Break in the pipelines of Sodium-cooled Fast Reactor. (November 2019) - Wu, Di; Gui, Minyang; Zhang, Jing; Wu, Yingwei; Wang, Chenglong; Wang, Mingjun; Su, G.H.
Highlights: The leak rate prediction models of LBB were established for SFR. The leak rate prediction program (LAPIS) for sodium pipelines was developed. The effects of crack morphology parameters on leak rate were studied. Abstract: The Leak Before Break (LBB) technology plays a vital role in the safety evaluation of Sodium-cooled Fast Reactor (SFR). In this study, the leak rate considered in LBB assessment of SFR was predicted and analyzed. Based on the models of fluid resistance in cracks, two-dimensional numerical simulation for leakage process of uniform cross-section axial cracks were conducted with Computational Fluid Dynamics (CFD) to obtain recommended values of crack empirical parameters, including entrance resistance coefficient, effective parameters and friction factors. With consideration of the complex crack morphologies, the leak rate prediction models with a wide range of parameters were established for liquid sodium, and corresponding computation code (LAPIS) was developed. The proposed models were verified and validated by seepage model, numerical results and experimental data with deviations within 1%, 35% and 10%, respectively. The effects of the crack morphology and thermal-hydraulic parameters on the leak rate for tight and wide cracks were studied with the LAPIS. The leak rate increases with Crack Opening Displacement (COD), crack length, ratio of entrance to exit area, entrance resistance coefficient, stagnation pressure and decreases with temperature. This work could provide theoretical and technical support for the study of leak rate considered in LBB assessment of SFR.